High plasma soluble thrombomodulin levels indicated poor prognosis of decompensated liver cirrhosis: a prospective cohort study. Issue 11 (5th August 2022) - Wei, Xinhuan; Du, Xiaofei; Liu, Yali; Wu, Jun; Zhang, Jing
Abstract : Objective: Hepatic sinusoidal endothelial injury is a prominent characteristic of liver cirrhosis. We determined plasma soluble thrombomodulin (sTM) levels in cirrhosis patients to evaluate the relationship between vascular injury and long-term prognosis. Methods: A prospective single-center study was performed. The participants were followed up for every 6 months or until death or transplantation. A chemiluminescent enzyme immunoassay was used to establish a baseline sTM. Results: Among the 219 patients with decompensated liver cirrhosis, 53.42% were caused by hepatitis B and hepatitis C. Plasma sTM levels were much higher in cirrhosis than in healthy controls and increased parallel with Child-Pugh classification ( P < 0.01) and the amount of ascites ( P = 0.04). After adjusting for sex, age, international normalized ratio, bilirubin, and other potential factors, multivariate Cox regression revealed that per TU/ml elevation of plasma sTM causes an increase of 8% in mortality, and per-SD elevation of thrombomodulin causes a 53% increase in mortality. As the mortality rates in low (5.90–12.60 TU/ml) and medium (12.70–18.00 TU/ml) sTM levels were similar, so we chose the cutoff of 18.00 TU/ml to divide into two groups, and K-M analysis indicated that patients with sTM >18.0 TU/ml demonstrated an additional 2.01 times death risk (95% CI, 1.13–7.93; P = 0.01) than those with sTM ≤18.0 TU/ml. Conclusion: Plasma sTM in cirrhosis was significantly increased in parallel with the severity of liver dysfunction. sTM elevation than 18 TU/ml indicated a poor prognosis of decompensated liver cirrhosis.